PENGUATAN KELOMPOK KOMPAS ALANG BERBASIS FIKIH EKOLOGI DI KAWASAN BENCANA LERENG KELUD KEDIRI - Abbas Sofwan Matlail Fajar; Reza Ahmad Zahid; Feny Tri Pujianingsih (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2024)
The focus of this service activity is to provide religious material and use local potential to carry out programs that have been planned with the ALANG Community. PKM activities are carried out using a PAR approach with the hope of maximizing the program created. The PKM results state that ecological fiqh is the basis for community empowerment as an effort to strengthen the integration of cultural and religious values ​​in environmental management carried out by the community. This program also encourages the formation of networks and collaboration between the community, government and various related parties in managing disaster-prone areas. This synergy strengthens empowerment and disaster risk management efforts, as well as facilitating access to resources and information needed for sustainable regional development. This Community Service Program has had a significant impact in increasing the resilience, welfare and independence of the Kelud slope community, as well as preserving the environment and local wisdom.